Chitosan a New Perspective towards Biotic and Abiotic Stress Management in Agriculture: A Review - Sirigireddy, Divya Vani; Kumari, Sudarshna; Datha, Mantramurthy Sri; Jincy, M.; Singh, Hanuwant; Bains, Gurdeep; Singh, K. P. (International Journal of Economic Plants, 2024)
Plant development and crop productivity are drastically reduced worldwide due to biotic and abiotic stresses and their unexpected combinations. The various chemicals (pesticides, fertilizers, and phyto-regulators) and genetic engineering techniques employed to date to improve crop tolerance to multiple stresses have a negative influence on the environment and are time-consuming. This has accelerated efforts to find more eco-friendly ways to control plant stress. Chitosan is a biopolymer which is largely extracted from the deacetylation of chitin and appears as a viable tool to overcome these problems in search of a more environmentally acceptable solution. Due to its biocompatibility, eco-friendly and economic nature, become one of the most popular biopolymers used in agriculture. Chitosan also activates a defence mechanism by signal transduction pathway and transduces secondary molecules of hydrogen peroxide and nitric oxide to scavenge reactive oxygen species. Application of chitosan before subjecting to abiotic stresses such as drought, salt, and heat has been shown to stimulate plant growth and enhance the production of antioxidant enzymes, secondary metabolites, and abscisic acid. In drought, it helps to accumulate osmo-protectants to maintain the water potential of plant cells. On the other hand, plant responses towards chitosan are varying based on its structures, doses, developmental stages and crop type. Keeping these facts in mind this review has written with the objective to update the recent studies on chitosan, its various sources and its effective concentrations in different crops, mechanism of action against biotic and abiotic stress management to improve crop production in agriculture.